STRATEGIES APPLIED BY ENGLISH TEACHERS IN EXPANDING STUDENT TALK IN CLASSROOM INTERACTION - Nindy Chairani; Zulhermindra Zulhermindra; Yulnetr Yulnetri (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
One of many roles of English teachers in the classroom is facilitating communication. An indication thatcommunication has been facilitated is the expansion of student talk. Expansion is a type of clause complex in logio-semantic relation of Systemic Functional Linguistics (Halliday and Matthiessen, 2014). However, in spite of many theories which promote the importance of student talk, classroom discourse is still dominated by English teachers. Phenomena which commonly found are the English teachers use mother-tongue language with the students, talk too much, and do not provide students sufficient time to response their statements and questions. Consequently, students use their mother tongue freely and give a single word or phrase in responding the teacher. However, brighter phenomena happened in two senior high schools in Tanah Datar Regency. Expanded student talk could be observed because the English teachers applied certain strategies. This paper aimed to describe strategies applied by English teachers in expanding student talk in classroom interaction. This paper employed qualitative method. The data were taken from interview result from 14 students 3 English teachers from two state senior high schools in Tanah Datar. To check the data trustworthiness, the source triangulation was employed. The result of this study revealed that there were eleven strategies applied by the English teachers: (1) Giving motivation, (2) Stating expectation, (3) Establishing rapport, (4) Giving meaningful feedback, (5) Holding discussion based activity, (6) Using interesting material, (7) Using understandable English language, (8) Asking referential question, (9) Establishing supportive environment, (10) Using body language, and (12) Extending wait time.